Evaluating the potential of pyriproxyfen dissemination using mosquito home system against Aedes albopictus at a dengue hotspot area - Ahmad Mohiddin Mohd Ngesom; Nazni Wasi Ahmad; Lee, Han Lim; Asmalia Md Lasim; Greenhalgh, David; Mazrura Sahani; Rozita Hod; Hidayatulfathi Othman (Penerbit Universiti Kebangsaan Malaysia, 2021)
Aedes mosquitoes were found to lay their eggs in the cryptic breeding sites. Eliminating cryptic and open breeding sites is essential in reducing dengue virus transmission. However, it is often challenging for health officers to assess these breeding sites which are usually missed during larval surveillance. The autodissemination approach may produce a better outcome by manipulating female mosquitoes to disperse insecticide to other Aedes spp. mosquito habitats. Thus, the present study aims to evaluate the effectiveness of the pyriproxyfen autodissemination technique using Mosquito Home System against the population of mosquitoes. This study was conducted in Bandar Baru Bangi, Selangor, Malaysia. The Mosquito Home System was deployed to control Aedes spp. populations at treatment sites using before-after-control-impact (BACI) design. The presence of pyriproxyfen distribution was confirmed using the WHO larval bioassay which resulted in 10-35% larvae mortalities. Autodissemination of pyriproxyfen significantly reduced the population size of mosquito eggs (p<0.05), larvae (p<0.05), and ovitrap index (p<0.05) at the treatment areas compared to the control areas. Moreover, rainfall was correlated positively against ovitrap index (r = 0.247), larvae (r = 0.420), and eggs (r = 0.422). The study provides promising results for controlling Aedes spp. populations and also highlights the potentials of this technique as an alternative in vector control programmes. However, further studies on larger scale field trials are warranted.